Chemistry of Chitosan Aerogels: Three‐Dimensional Pore Control for Tailored Applications. Issue 18 (30th November 2020) - Takeshita, Satoru; Zhao, Shanyu; Malfait, Wim J.; Koebel, Matthias M.
Abstract: Chitosan is an abundant biopolymer derived from food waste with attractive properties, particularly its high biocompatibility and easy chemical processability. Here, we review the rapidly expanding literature on chitosan‐based porous materials with a focus on the gelation mechanisms, the three‐dimensional multiscale structural control, and the diverse chemical functionality not accessible by other biopolymers. The properties vary widely: from supercritically dried, mesoporous chitosan aerogels to very light, freeze‐dried macroporous scaffolds. Porous chitosan displays impressive performance at the laboratory scale, but the highly (meso)porous nature amplifies not only the beneficial functionality of chitosan, but also its drawbacks, resulting in serious barriers to industrialization. In order to facilitate technology transfer, we critically discuss the practical feasibility of chitosan aerogels in potential applications compared to conventional and other biopolymer‐based porous or nonporous materials. Abstract : Chitosan aerogels and freeze‐dried gels—these fascinating bio‐derived materials, with tailored porous structures and otherwise inaccessible functionalities, recently emerged from the biomedical field into the realm of materials science and chemistry. Chitosan aerogels are a hot topic in academic research, but what are the barriers to industrial production and commercialization?